Workplace bullying-A case study on RHB Bank Berhad, Malaysia - Thamarakshan, Shalima (2015)
This study aimed to determine if workplace bullying occurs at RHB Bank Berhad. In addition, this study also analyzed if there was a significant relationship between workplace bullying and the respondents’ demographic information such as age, gender, race, years of employment and position. Types of bullying are divided into six forms, namely work-related bullying, personal attacks, social isolation, verbal aggression, physical aggression and the spreading of rumours. A total of 100 questionnaires were selected by random cluster sampling of the group and distributed, whereby 76 employees of RHB Bank branches at Pantai Lebuh and Jelutong, Penang and Bakar Arang , Sungai Petani responded. The instrument used in this study was the slightly modified set of questionnaires NAQ (Negative Acts Questionnaire) accordingly. The data obtained were processed collectively using the Statistical Package for Social Sciences (SPSS) version 19. Statistical techniques used were frequency, percentage, mean, median, standard deviation, Hypothesis Testing and Pearson’s Correlation. Based on the analysis of the questionnaires, it was shown that there exists a significant relationship between gender, job designation and duration of employment with workplace bullying. Race and age, however, did not seem to have a significant relationship with workplace bullying